Impaired chromatin remodelling at STAT1-regulated promoters leads to global unresponsiveness of Toxoplasma gondii-infected macrophages to IFN-γ. - Christine Lang (Public Library of Science (PLoS), 2012)
Intracellular pathogens including the apicomplexan and opportunistic parasite Toxoplasma gondii profoundly modify their host cells in order to establish infection. We have shown previously that intracellular T. gondii inhibit up-regulation of regulatory and effector functions in murine macrophages (MΦ) stimulated with interferon (IFN)-γ, which is the cytokine crucial for controlling the parasites' replication. Using genome-wide transcriptome analysis we show herein that infection with T. gondii leads to global unresponsiveness of murine macrophages to IFN-γ. More than 61% and 89% of the transcripts, which were induced or repressed by IFN-γ in non-infected MΦ, respectively, were not altered after stimulation of T. gondii-infected cells with IFN-γ. These genes are involved in a variety of biological processes, which are mostly but not exclusively related to immune responses. Analyses of the underlying mechanisms revealed that IFN-γ-triggered nuclear translocation of STAT1 still occurred in Toxoplasma-infected MΦ. However, STAT1 bound aberrantly to oligonucleotides containing the IFN-γ-responsive gamma-activated site (GAS) consensus sequence. Conversely, IFN-γ did not induce formation of active GAS-STAT1 complexes in nuclear extracts from infected MΦ. Mass spectrometry of protein complexes bound to GAS oligonucleotides showed that T. gondii-infected MΦ are unable to recruit non-muscle actin to IFN-γ-responsive DNA sequences, which appeared to be independent of stimulation with IFN-γ and of STAT1 binding. IFN-γ-induced recruitment of BRG-1 and acetylation of core histones at the IFN-γ-regulated CIITA promoter IV, but not β-actin was diminished by >90% in Toxoplasma-infected MΦ as compared to non-infected control cells. Remarkably, treatment with histone deacetylase inhibitors restored the ability of infected macrophages to express the IFN-γ regulated genes H2-A/E and CIITA. Taken together, these results indicate that Toxoplasma-infected MΦ are unable to respond to IFN-γ due to disturbed chromatin remodelling, but can be rescued using histone deacetylase inhibitors.